LEJEUNEACEAE (SUBFAMILY: LEJEUNEOIDEAE) OF MOUNT SIBUATAN, NORTH SUMATRA, INDONESIA - Ferdinand Susilo; Nursahara Pasaribu; Syamsuardi Syamsuardi; Etti Sartina Siregar (PTTI, 2023)
Lejeuneaceae (Subfamily: Lejeuneoideae) of Mount Sibuatan, North Sumatra, Indonesia. Information on the local diversity of the subfamily Lejeuneoideae in North Sumatra, Indonesia, is still less reported, especially in Mount Sibuatan. This study aimed to collect, explore and describe the morphological characters and obtain the diversity of the subfamily Lejeuneoideae in the Mount Sibuatan forest area, North Sumatra. Nineteen species of this subfamily are reported, comprising eight genera: Cheilolejeunea, Cololejeunea, Colura, Diplasiolejeunea, Drepanolejeunea, Lejeunea, Metalejeunea, and Pycnolejeunea.. One species, namely Drepanolejeunea pentadactyla, is reported as new record for Sumatra. Identification key to species and pictures of species newly recorded is provided.